The Role of Housewife to Improve the Sustainability of the Cipatani River (Study in Nangewer Village, Pagerageung District, Tasikmalaya Regency) - Fadjarajani, Siti; Indrianeu, Tineu (Jurnal Pendidikan Geografi Gea, 2021)
The existence of rivers is very important in the life of the ecosystem on earth, where in the hydrological conditions the river is one of the important places for the flow of water on earth which will be discharged into the sea. However, the current condition of the river is very worrying, because the river is used as a place for waste disposal, both industrial and household waste. In Nangewer Village, Pagerageung District, Tasikmalaya Regency, a group of housewives who are members of the Srikandi Sungai Indonesia group took the initiative to improve the sustainability of the river. The group of housewives plays a role in river conservation efforts such as cleaning the river, arranging rivers, and maintaining the for the better quality of river water. The aims of this research are to carry out the role and efforts of housewives in preserving the Cipatani river. Based on the results, there are a group of housewives, they made efforts in the form of river conservation, including periodic cleaning of the river, planting plants / trees along the river to reduce soil erosion and sedimentation, organize, and tidy up the river so that it becomes more beautiful.